The Global Burden of Polycystic Ovary Syndrome in Women of Reproductive Age: Findings from the GBD 2019 Study - Jiang B (International Journal of Women's Health)
Bengui Jiang Department of Gynecology and Obstetrics, Ningbo University’s Women’s and Children’s Hospital, Ningbo, Zhejiang, 315000, People’s Republic of ChinaCorrespondence: Bengui Jiang, Department of Gynecology and Obstetrics, Ningbo University’s Women’s and Children’s Hospital, Ningbo, Zhejiang, 315000, People’s Republic of China, Email jiangbengui@126.comPurpose: Polycystic ovary syndrome (PCOS) is a prevalent endocrine disorder and the primary cause of anovulatory infertility among women aged 15– 49 years. Despite its significance, it has been largely overlooked in global health discussions, with persistently high prevalence and incidence rates. This public health challenge necessitates attention both domestically and internationally. Between 1990 and 2017, the age-standardized prevalence of female infertility and associated DALYs rose by 0.70% and 0.396%, respectively. Economically, addressing women’s endocrine and metabolic health can bolster the overall well-being of the female population using existing resources. For judicious utilization of available resources, data regarding the burden of PCOS is pivotal for comprehending women’s health status and for devising and refining policies related to women’s endocrine health. Consequently, this study scrutinizes and assesses the age-standardized PCOS incidence rate and DALYs for 1990 and 2019, traces the trends of these metrics from 1990 to 2019, examines the composition of various populations and diseases, and offers international comparisons. This aims to furnish critical insights for future health policy development and adjustments in the realm of female endocrine and metabolic health.Patients and Methods: This study employed the Global Health Data Exchange to obtain PCOS burden data based on GBD 2019. It collected incidence, DALYs, and age-standardized rates (ASRs) from 1990 to 2019 across global, regional, national, and SDI quintile levels, spanning 21 regions and 204 countries. To analyze trends, ASRs and estimated annual percentage changes (EAPCs) were calculated, with standardization crucial for comparability. EAPC was derived using a generalized linear model with a Gaussian distribution.Results: The global burden of PCOS increased significantly from 1990 to 2019, with estimated annual percentage change (EAPCs) of 0.56 for incidence and 0.83 for DALYs. The highest incidence rates were observed in the High-income Asia Pacific region, particularly in Japan and New Zealand, while the lowest rates were in Central Europe. Equatorial Guinea and Qatar exhibited the most pronounced increases in incidence and DALYs, attributed to urbanization and enhanced healthcare infrastructure. The incidence and DALYs of PCOS showed variation across SDI quintiles, with the greatest burden found in the middle-SDI quintile. Women between the ages of 20– 29 years had the highest incidence and DALYs, emphasizing the importance of targeted interventions during this critical period. In contrast, regions with lower SDI levels, such as Central and Eastern Europe, reported the lowest burdens of PCOS, likely due to underdiagnosis and limited healthcare resources.Conclusion: From 1990 to 2019, there was a significant increase in the global burden of PCOS, with variations seen across regions and SDI quintiles. Countries such as Italy, Japan, New Zealand, and Australia had the highest burdens, while Central and Eastern Europe had the lowest. The age group most affected was women aged 20– 29 years, emphasizing the necessity for targeted interventions.Keywords: reproductive age, polycystic ovary syndrome, incidence, disability-adjusted life-years, socio-demographic index